The Influence of Family Sports Attitude on Children’s Sports Participation, Screen Time, and Body Mass Index - Lian, Yin; Peijie, Chen; Kun, Wang; Tingran, Zhang; Hengxu, Liu; Jinxin, Yang; Wenyun, Lu; Jiong, Luo (Frontiers in Psychology, 2021)
Background: Children’s physical health is an important resource for a country’s future construction. However, researchers found that the physical fitness of young children around the world has declined during the two decades, from 1992 to 2012. The decline in the physique of young children has caused widespread concern around the world. Children’s main living places are families and kindergartens, so this research explores the impact of family factors on children’s body mass index (BMI) from the perspective of family attitudes, children’s sports participation, and screen time. Methods: A cross-sectional study was used to conduct a questionnaire survey of children in China. A total of 600 children were investigated, and 589 valid questionnaires were obtained. SPSS21.0 statistical analysis software was used for descriptive analysis, mean comparison, and correlation analysis of the data. AMOS 21.0 was used to construct a structural equation model and carry out path analysis. Results: (1) There are significant differences in children’s family sports attitude, sports participation, screen time, and BMI with different family structures, and parents’ education levels. (2) Family sports attitude is significantly positively correlated with parents’ education levels and children’s sports participation, and negatively correlated with children’s screen time and BMI. (3) Children’s sports participation and screen time play a chain-mediating role between family sports attitude and children’s BMI, and the role is a complete mediating role. Therefore, family sports attitudes can affect children’s physical health by affecting children’s sports participation and screen time. To promote children’s physical health, we should pay attention to the intervention of family sports attitude. (4) The mediating effects of exercise participation and screen time are similar in different family structures, so the structure of this study can be applied to different family structures. Conclusions: Children’s family sports attitude, sports participation, and screen time can affect children’s BMI. Children’s screen time and sports participation play a chain-mediating role in the influence of family sports attitudes on the path of children’s BMI. The results of this study will provide a useful reference for teachers and parents to control children’s physical health.